2011
DOI: 10.1021/ja201403q
|View full text |Cite
|
Sign up to set email alerts
|

Can Amorphous Nuclei Grow Crystalline Clathrates? The Size and Crystallinity of Critical Clathrate Nuclei

Abstract: Recent studies reveal that amorphous intermediates are involved in the formation of clathrate hydrates under conditions of high driving force, raising two questions: first, how could amorphous nuclei grow into crystalline clathrates and, second, whether amorphous nuclei are intermediates in the formation of clathrate crystals for temperatures close to equilibrium. In this work, we address these two questions through large-scale molecular simulations. We investigate the stability and growth of amorphous and cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
194
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(213 citation statements)
references
References 37 publications
18
194
1
Order By: Relevance
“…The coarse-grained mW water was used in previous studies to investigate the stability, growth, and nucleation of clathrate hydrates. 10,29,52,[54][55][56][57][60][61][62] In this work, we show that, under conditions of identical driving force, the sII clathrate crystal is the fastest growing polymorph followed by the TS, HS-I, and sI crystals. We find that nucleation and growth of a distinct interfacial transition layer at the seed/liquid interface is necessary in order for cross-nucleation to occur from or to sII and any of TS, HS-I, and sI, but not among the latter three.…”
Section: Introductionmentioning
confidence: 54%
“…The coarse-grained mW water was used in previous studies to investigate the stability, growth, and nucleation of clathrate hydrates. 10,29,52,[54][55][56][57][60][61][62] In this work, we show that, under conditions of identical driving force, the sII clathrate crystal is the fastest growing polymorph followed by the TS, HS-I, and sI crystals. We find that nucleation and growth of a distinct interfacial transition layer at the seed/liquid interface is necessary in order for cross-nucleation to occur from or to sII and any of TS, HS-I, and sI, but not among the latter three.…”
Section: Introductionmentioning
confidence: 54%
“…For methane hydrates, using biased MD (owing to the larger free energy barriers involved for nucleation vis-à-vis the more hydrophilic, electrostatically interacting, and dipolar H 2 S in H 2 S clathrate), a marked kinetic preference for sII-like nano-crystallites is evident, despite sI being the thermodynamically stable form. 25 At first glance, this may seem somewhat surprising, but this exploration of other shapes, or indeed (quasi-) amorphous structures during nucleation has been observed, 9,10,[13][14][15][16]25 owing to relatively accessible free-energy barriers in between different cage motifs and polymorphic environments.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 A unit cell in sII hydrate consists of 136 water molecules forming sixteen small 5 12 cages and eight large hexadecahedral 5 12 6 4 cages. 1,2 In recent years, the molecular simulation of clathrate hydrates has revealed much about their structural properties, 3 and Monte Carlo 4 and molecular dynamics (MD) simulations, whether brute force (i.e., standard) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or biased, [22][23][24][25] of hydrate formation have revealed a propensity for either (approximately) sI or sII polymorphs to form, despite one form typically being most thermodynamically stable for a given guest type (and temperature/pressure). Given that such simulation can provide molecular-level insights into hydrate-formation dynamics, this allows for probing the structural nature of the growing hydrate a) Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Theoretically, the nucleation and growth process of methane hydrate have been simulated and explored on the atomic and molecular level through molecular dynamics simulations. [23][24][25][26][27][28][29][30] The interaction between host water cages and guest molecules, 32,41 stability, diffusion and vibrations of guest molecules in water cavities of clathrate hydrates, 31,34,[38][39][40][42][43] and phase transition between ice and methane clathrates have been studied by firstprinciple calculations. 37,44 Experimentally, Raman spectra of hydrocarbon hydrates have demonstrated that the CH stretching frequency of the guest molecule is commonly (but not always) lower when in a large cage than when in a small cage [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%